Discovery of highly divergent lineages of plant-associated astro-like viruses sheds light on the emergence of potyviruses - Lauber, Chris; Bartenschlager, Ralf; Seitz, Stefan (Virus research, 2019)
RNA viruses are believed to have originated from a common ancestor, but how this ancestral genome evolved into the large variety of genomic architectures and viral proteomes we see today remains largely unknown. Tackling this question is hindered by the lack of universally conserved proteins other than the RNA-dependent RNA polymerase (RdRp) as well as a limited RNA virus sampling. The latter is still heavily biased towards relatively few viral lineages from a non-representative collection of hosts, which complicates studies aiming to reveal possible trajectories during the evolution of RNA virus genomes that are favored over others. We report the discovery of 11 highly divergent lineages of viruses with genomic architectures that resemble those of the astroviruses. These genomes were initially identified through a sequence homology search in more than 6600 plant transcriptome projects from the Sequence Read Archive (SRA) using astrovirus representatives as query. Seed-based viral genome assembly of unprocessed SRA data for several dozens of the most promising hits resulted in two viral genome sequences with full-length coding regions, nine partial genomes and a much larger number of short sequence fragments. Genomic and phylogenetic characterization of the 11 discovered viruses, which we coined plastroviruses (plant-associated astro-like viruses), showed that they are related to both astro- and potyviruses and allowed us to identify divergent Serine protease, RdRp and viral capsid domains encoded in the plastrovirus genome. Interestingly, some of the plastroviruses shared different features with potyviruses including the replacement of the catalytic Ser by a Cys residue in the protease active site. These results suggest that plastroviruses may have reached different points on an evolutionary trajectory from astro-like to poty-like genomes. A model how potyviruses might have emerged from (pl)astro-like ancestors in a multi-step process is discussed.
Available online 16 November 2018
Gesehen am 15.03.2019